Sports Injuries and the Right to Damages - Sadler, Pauline; Guthrie, Rob (2001)
This article examines the availability of damages at common law for injured sportspersons and the potential liability of employers, organisers, and facility providers in the sporting industry. The article discusses the common law action of the torts of negligence and trespass are considered. Cases discussed include: Agar v Hyde; Rogers v Budgen; Noak v Waverley Municipal Council; Bartels v Bankstown City Council; and McNamara v Duncan.